Good Governance in National Defense Management: Challenges and Policy Directions in Indonesia - Nugroho, Anton (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2025)
The application of good governance principles in national defense management has become a crucial issue in democratic state governance. The defense sector has unique traits due to its direct link to national security and strategic confidentiality, yet it is increasingly expected to adhere to principles of transparency, accountability, effectiveness, rule of law, and civilian oversight. This article aims to analyze how well good governance principles are implemented in Indonesia’s defense management, identify main challenges that remain, and propose policy directions to improve defense governance in the future. This study used a qualitative approach, based on a review of laws and regulations, official policy documents, audit reports, and academic literature on defense governance. The findings show that although Indonesia has established a relatively clear legal and institutional framework, there are still challenges in transparency of the defense budget, governance of major weapon system procurement, civilian oversight effectiveness, and strengthening organizational integrity within defense institutions. Improving accountability systems, leveraging information technology in defense management, and boosting the capacity of oversight agencies are key strategic steps toward on a professional, efficient, and publicly trusted defense system governance.